Toxicological landscape of Fuzi: a comprehensive study on the spatial distribution of toxicants and regional neurotoxicity variability in zebrafish - Xiaoqi Pan; Xiaoqi Pan; Tianyu Liang; Han Feng; Weiying Liu; Qiaoxin Mou; Xiaoyu Yan (Frontiers in Pharmacology)
Fuzi, a Chinese herb widely used in clinical settings, exhibits varying levels of toxicity depending on its geographical origin. Diester-type alkaloids are the primary contributors to the toxicity of Fuzi. This study aims to investigate regional differences and underlying mechanisms of Fuzi-induced neurotoxicity across China. Matrix-assisted laser desorption/Ionization mass spectrometry imaging (MALDI-MSI) method was employed to map the spatial distribution of six key diester-type alkaloids from Fuzi samples originating from five major regions. The results showed that the diester-type alkaloids were primarily distributed in the cuticle of Anguo- and Ludian-Fuzi, in the cuticle, cork, and pith of Butuo-Fuzi, in the phloem and pith tissues of Chenggu-Fuzi, and in the cuticle, cork, inner phloem, and pith of Jiangyou-Fuzi. When zebrafish were exposed to a Fuzi decoction for 24 h, it was observed that Jiangyou-Fuzi induced the most significant neurobehavioral abnormalities, lipid peroxidation damage, and aberrant neurotransmitters release. RNA sequencing analysis further indicated that the amino acid metabolism, ErbB, cGMP-PKG, and p53 signaling pathways-regulated by changes in the expression of Glub, Mao, GAB1, PRKG1B, PSEN2, and BAXα genes were disrupted to varying extents by Fuzi from different origins. In summary, the regional variability in the neurotoxicity of Fuzi can be attributed to differences in the distribution of its active compounds and underlying mechanisms. Among the samples tested, Jiangyou-Fuzi exhibited the highest neurotoxicity, followed by Anguo-, Chenggu-, Ludian-, and Butuo-Fuzi.